Combining ability and gene action for yield improvement in kenaf (Hibiscus cannabinus L.) under tropical conditions through diallel mating design - Md Al‑Mamun; Rafii, Mohd Y.; Misran, Azizah; Berahim, Zulkarami; Ahmad, Zaiton; Hasan Khan, Md Mahmudul; Oladosu, Yusuff (Nature Research, 2022)
Nine morphologically distinct kenaf genotypes were hybridized to produce 36 hybrids following a half diallel mating design. The combining ability and gene action of 15 yield and yield components were assessed in hybrids and their parents across two environments. Except for the mid diameter and plant height traits, there were highly significant differences (p ≤ 0.01) between the environments and the interaction of genotype and environment. Additive gene effects were considerable for the inheritance of these traits, and the expression of these additive genes was heavily influenced by the environment. Significant differences were found for all studied traits for GCA except top diameter and SCA except plant height and top diameter, implying the presence of both additive and non-additive gene action for the inheritance of the concerned characters. For all features except top diameter and number of nodes, the magnitude of GCA variation was significantly higher than that of SCA variance, indicating the additive gene's predominance. The parental lines P1, P3 and P4 were outstanding general combiners for fiber yield and yield-related parameters. Considering combining ability and genetic analysis study, the crosses P1 × P4, P1 × P9, P2 × P3, P2 × P5, P4 × P6, P4 × P7, P4 × P9, P5 × P8, and P7 × P9 were found promising for their heterotic response to higher fiber yield, stick yield, seed yield and could be for future improvement in kenaf breeding programmes.